Universities, Funding Systems, and the Renewal of the Industrial Knowledge Base – UNI Project Findings - Terttu Luukkonen (The Research Institute of the Finnish Economy (ETLA), 2014)
An important prerequisite for the renewal of Finland's industrial and economic base is the ability of the universities to promote the renewal of the knowledge base. The UNI project studied ways in which changes in external funding mechanisms and recent governance changes in Finnish universities have changed the framework conditions influencing innovativeness and innovation in university research. Innovation here refers to novel approaches and potentially, breakthrough research, requiring risk-taking. The UK provided a comparative perspective for the study. This report reprints four separate policy briefs and reports that the UNI project has produced and provides an overall concluding chapter for them. A major conclusion of the study is that, so far, there has not been much impact from the recent policy changes on intellectual innovation in research in Finland. University governance influences research content very indirectly and is mediated by multiple other factors, meaning that policy changes are not, at least in the short run, translated into changed research content. As far as research funding organisations are concerned, Finland has not had a funding organisation that encourages risk-taking and intellectual innovation in research. Recent policy changes have not fundamentally altered this situation. In the UK, the established practice of performance measurement of universities seems to narrow notions of appropriate research content and standards of performance and is becoming an ominous factor in reducing variety and risk-taking in university research. This phenomenon is further developed in the UK, but Finland seems now to be `catching up'. In industry-university collaboration short-term commissions and most of Tekes' industrial collaboration support draw on existing knowledge and know-how and are not intended to promote highly innovative and high-risk activities. More flexible and longer-term contracts can in principle promote such research activities provided that the knowledge they produce will be in the public arena since scientific breakthroughs, to bear fruit, require a great deal of further development and wide adoption of the novel concepts, methods etc. by the scientific community.
Keywords: O38; O39; 330; University research; Research funding; Intellectual innovation in research; University governance; Universitäre Forschung; Forschungsfinanzierung; Hochschulpolitik; Technologiepolitik; Finnland; Vergleich; Großbritannien